Exploring Sentinel-1 and Sentinel-2 time series sensitivity to rice height - Abdikan, Saygin; Ganeva, Dessislava; Narin, Omer Gokberk; Sekertekin, Aliihsan; Dimitrov, Zlatomir; Bayik, Caglar; Chanev, Milen; Filchev, Lachezar; Ustuner, Mustafa; Esetlili, Mustafa Tolga; Sanli, Fusun Balik; Kurucu, Yusuf (IEEE, 2024)
The rice plant is one of the most widely consumed crops globally, and its height is a key indicator of growth. This study explored the relationship between rice plant height, measured in situ in Bulgaria and Turkiye, and multi-temporal data from Sentinel-1 and Sentinel-2 satellites to develop models for height estimation. The strongest correlation was observed when integrating the Radar Vegetation Index (RVI) and the Normalized Difference Vegetation Index (NDVI), yielding a correlation coefficient of r = 0.69. Additionally, using VV polarization in a multi-linear regression analysis resulted in the lowest error rate, with a root mean square error (RMSE) of 14.14 cm. The findings suggest that combining synthetic aperture radar (SAR) and optical data holds significant potential for accurately estimating rice plant height.
Keywords: paddy rice; crop phenophase; Sentinel-1; Sentinel-2; remote sensing; Agriculture